2017
DOI: 10.1038/srep45507
|View full text |Cite
|
Sign up to set email alerts
|

Protein S Heerlen mutation heterozygosity is associated with venous thrombosis risk

Abstract: Hereditary Protein S (PS) deficiency is a rare coagulation disorder associated with an increased risk of venous thrombosis (VT). The PS Heerlen (PSH) mutation is a rare S501P mutation that was initially considered to be a neutral polymorphism. However, it has been later shown that PSH has a reduced half-life in vivo which may explain the association of PSH heterozygosity with mildly reduced levels of plasma free PS (FPS). Whether the risk of VT is increased in PSH carriers remains unknown. We analyzed the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…The most strongly associated rare (MAF < 0.01) variant we observed was rs121918472 (OR: 1.93; 95% CI: 1.46–2.56; P = 3.55 × 10 −6 ), a nonsynonymous variant located in the Protein S ( PROS1 ) gene, also known as the p.Ser501Pro or PS Herleen mutation, MAF = 0.005. This variant is also known to be associated with VTE (Suchon et al, ). After excluding known loci, only one single variant remained significant after adjusting for multiple testing but this signal was driven exclusively by the MARTHA study ( p = 1.96 × 10 –15 when including MARTHA and p = 0.37 after excluding MARTHA).…”
Section: Resultsmentioning
confidence: 99%
“…The most strongly associated rare (MAF < 0.01) variant we observed was rs121918472 (OR: 1.93; 95% CI: 1.46–2.56; P = 3.55 × 10 −6 ), a nonsynonymous variant located in the Protein S ( PROS1 ) gene, also known as the p.Ser501Pro or PS Herleen mutation, MAF = 0.005. This variant is also known to be associated with VTE (Suchon et al, ). After excluding known loci, only one single variant remained significant after adjusting for multiple testing but this signal was driven exclusively by the MARTHA study ( p = 1.96 × 10 –15 when including MARTHA and p = 0.37 after excluding MARTHA).…”
Section: Resultsmentioning
confidence: 99%
“…As an example, Suchon et al . demonstrated that the PROS1 Heerlen mutation was associated with an OR for VT of ∼6 but a moderate decrease in free PS levels (∼ 70%)(Suchon et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two of these genes ( PROS1 and SERPINC1 ) have been found to harbour less uncommon polymorphisms that also modulate the susceptibility to VTE. As far PROS1 is concerned, a meta‐analysis of 4 French case‐control studies for VTE demonstrated that the rs121918472, also referred to as the Protein S Heerlen mutation, a non synonymous Serine to Proline (Ser501Pro) substitution with a frequency of <1% in the general population and previously considered as a benign polymorphism, was associated with an ~6‐fold increased risk of VTE (Suchon et al , ). The rs121918474 (Lys196Glu) is another PROS1 coding mutation associated with increased risk of VTE [odds ratio (OR) ~5] by lowering PS anticoagulant activity but this mutation is specific to the Japanese population, approximately 1/12 000 individuals being homozygous for the 196Glu allele (Kimura et al , ; Liu et al , ).…”
Section: Established Venous Thrombosis‐disease Genes and Their Suscepmentioning
confidence: 99%